Reserve levels and intraday federal funds rate behavior - Spence Hilton; Warren B. Hrung (Federal Reserve Bank of New York, 2007)
We analyze the impact of aggregate reserve levels on the intraday behavior of the federal funds rate over a sample period extending from 2002 to 2005. We study both how the reserve levels accumulated earlier in a maintenance period influence the morning level of the funds rate relative to the target set by the FOMC, and how same-day reserve levels as well as the reserve levels accumulated earlier affect intraday movements of the funds rate. The impact of recurring calendar events on the behavior of the federal funds rate is also explored. In general, we find a negative relationship between our measures of reserve levels and our two measures of federal funds rate behavior.
Keywords: E5; G21; 330; federal funds rate; open market operations; reserve requirements; Geldmarkt; Bankenliquidität; Offenmarktpolitik; USA